A review on biodegradation and photocatalytic degradation of organic pollutants: A bibliometric and comparative analysis - Singh P.; Borthakur A. (My University, 2025)
In the present era, environmental pollution are increasing manifolds due to various anthropogenic activities. Organic pollutants are one of the biggest nuisances faced by the present human population. Several measures have been proposed and applied for their abatement. Organic pollutants released from the various activities of petrochemicals pose a serious concern among the scientists and researchers. Petrochemicals pollutants are considered as toxic, carcinogenic and hazardous. Therefore their abatement is need of hours with the efficient and sustainable techniques. It was found that recent research activities/publications are increasing on these topics due to various environmental problems. Biodegradation and photodegradation seem to be the most favorable technique for the degradation of wastewater contaminated with petrochemicals. In the present study, our approach was to comparatively evaluate these two most adopted processes i.e. biodegradation and photocatalytic degradation through content and bibliometric and analysis. Firstly Bibliometric analysis was performed on the literature cited in Scopus, for elucidating the present research trend. Both the processes are accepted even at pilot scale and have some limitations and advantages. Biodegradation processes are known as sustainable processes for the abatement of environmental pollution and even for petroleum industrial wastewater treatment at large scale. However, a various problem associated with these processes such as their low efficiency, microbial specificity to pollutants and sensitivity to the environmental factor in case of biodegradation and high running cost, need skilled man-power, and sometimes, intermediates are also more toxic than original pollutants in case of Photocatalytic processes. Based on our comparative evaluation of these two processes, we concluded that there is need of more research on both these technique. And there is a possibility of hybrid of two existing processes. © 2018 Elsevier Ltd